Asuhan Keperawatan Pada Ny. S Keluarga Tn. F Dengan Gangguan Sistem Kardiovaskular : Hipertensi Di Desa Karang Jati RT 01 RW 05 Kecamatan Tonjong Kabupaten Brebes - Muhammad Anas Al Mahdi; Lina Farikha (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Background: Non-communicable diseases (NCDs) are a major global public health concern, with hypertension affecting an estimated 1.4 billion adults worldwide. In Indonesia, the prevalence of hypertension among individuals aged 18 years and above reached 30.8% in 2023. In Kecamatan Tonjong, Kabupaten Brebes, the number of hypertension sufferers aged 15 years and above reached 15,951 people in 2025. Objective: To implement comprehensive family nursing care for Ny. S, family of Tn. F, who experienced cardiovascular system disorders due to hypertension in Desa Karang Jati RT 01 RW 05, Kecamatan Tonjong, Kabupaten Brebes. Method: This study used a descriptive narrative method with a nursing process approach (assessment, diagnosis, intervention, implementation, and evaluation), conducted through home visits over three days from December 26–28, 2025. Data were collected through interviews, observation, physical examination, and documentation. Results: Two nursing diagnoses were identified: acute pain related to hypertension and knowledge deficit regarding hypertension. Nursing interventions included pain management, oral medication administration (captopril 25 mg), and health education. Complementary non-pharmacological therapy using cucumber juice was applied once daily for three days. Conclusion: After three days of nursing implementation, both nursing diagnoses were fully resolved. Blood pressure decreased from 165/90 mmHg to 132/77 mmHg and the pain scale reduced from 4 to 1. Discharge planning was provided including recommendations for routine blood pressure monitoring, healthy lifestyle, and consistent medication adherence.